Epidemiological characteristics and risk factors of severe asthma in children: a single-center prospective cohort study - WANG Yingwen; LI Xiaoling; DAI Jiajia; LIU Fang; HUANG Jianfeng; WANG Libo; ZHANG Xiaobo; FENG Rui (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To explore the epidemiological characteristics of severe asthma in children and analyze the risk factors.Methods·A single-center prospective cohort study was conducted. Six hundred and seventy four children with difficult-to-treat asthma who visited the Children´s Hospital of Fudan University from January 1 to December 31, 2021 were included to establish a dynamic cohort. Basic information (including gender, age, gestational age at birth, birth weight, etc.) and comorbidity of the cohort members were collected. The asthma control status, drug inhalation technique level, medication compliance, pulmonary function parameters [forced expiratory volume in one second (FEV1) as a percent-age of the predicted value (FEV1%pred), FEV1/ forced vital capacity (FVC), and the rate of estimated values of forced expiratory flow at 50% of FVC exhaled (FEF50), FEF75, and FEF25-75 in percent-predicted value, respectively], airway inflammation index [fraction exhaled nitric oxide (FeNO)], and allergy status parameters [eosinophil (EOS) and immunoglobulin E (IgE)] of all cohort members were evaluated. All cohort members underwent re-evaluation respectively at the specialist asthma clinic of the hospital at 3, 6, 9, and 12 months.Results·At the endpoint of the cohort, 52 children were diagnosed with severe asthma, accounting for 7.7%. A high proportion of severe asthma was found in children who were exposed to secondhand smoke, used air conditioning at home all year round, or had coexisting rhinitis/nasosinusitis, FEV1%pred<80%, FEV1/FVC<80%, small airway dysfunction, EOS>300/μL, IgE>200 IU/L, or FeNO>20/25 ppb [FeNO>20 ppb (≤12 years old) or >25 ppb (>12 years old), 1 ppb=1×10-9 mol/L]. A high proportion of non-severe asthma was found in children who were breastfed for 6 months or longer, or had good medication compliance. The differences were statistically significant (all P<0.05). There were more males in children with severe asthma aged 6‒11 years, and more females in children with severe asthma aged 12‒17 years, with statistical significance (both P<0.05). Multiple-factor Logistic regression analysis showed that only small airway dysfunction was an independent risk factor for severe asthma [OR=5.158 (95%CI 2.516‒10.572)].Conclusion·The proportion of children with severe asthma has a significantly decrease after one year of standardized management in children with difficult-to-treat asthma. Small airway dysfunction is an independent risk factor for the progression to severe asthma.